Students’ Perception of Using TED Talks on Speaking Skill in English language Teaching - Lidia Dwi Permatasari; Fera Zasrianita; Hanura Febriani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to explore students’ perceptions of using TED Talks as a medium to improve speaking skills in English Language Teaching. The study was conducted on second-semester students of the English Education Study Program at UIN Fatmawati Sukarno Bengkulu in the academic year 2024/2025. The research employed a qualitative approach with a case study design. Data were collected through questionnaires, interviews, and observations. The findings revealed that most students perceived TED Talks positively. They found the videos to be motivating, informative, and effective in enhancing vocabulary, pronunciation, and speaking confidence. TED Talks also exposed students to authentic language use and public speaking models. However, some challenges were identified, including difficulties in understanding native speakers’ accents, rapid speech, and technical limitations. Therefore, it can be concluded that integrating TED Talks into speaking classes can significantly improve EFL students’ speaking skills if supported by purposeful teaching practices.